Team physician consensus statement: Return to sport/return to play and the team physician: A team physician consensus statement - 2023 update - Herring, S. A.; Putukian, M.; Kibler, W. B.; LeClere, L.; Boyajian-O`Neill, L.; Day, M. A.; Franks, R. R.; Indelicato, P.; Matuszak, J.; Miller, T. L.; O`Connor, F.; Poddar, S.; et al. (Current Sports Medicine Reports, 2024)
Return to play (RTP) is the process of returning an athlete to participate in his/her/their sport. Return to sport (RTS) is applicable to all sports and athletes. For the purposes of this consensus statement, RTS will be used to include both the process and the decision, focused on non-game-day RTS. It is important for the team physician to recognize RTS represents a continuum: return to participation, RTS, and return to performance. This progression can be applied for any sport, athlete, or injury/illness. The RTS decision is ongoing, is context dependent, and may change over time.